2021
DOI: 10.9734/jpri/2021/v33i59b34356
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Pelvic Proprioceptive Neuromuscular Facilitation Techniques on Balance and Gait Parameters in Children with Spastic Diplegia: A Study Protocol for a Randomized Clinical Trial

Abstract: Background: Cerebral Palsy is a spacious term which highlights an extensive gamut of motor affliction which has a stagnant tendency. The estimated Cerebral Palsy is indeed very prevalent in developed nations 2 out of the next 1000 live births and neonatal survivors. Among several Cerebral Palsy comes in a variety of manifestations. Spastic Diplegia is common in a majority of Preterm babies. Several treatment strategies of Physical therapy are utilized for Spastic Diplegia. This research focusses on assessing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…Hearing preservation and treatment-related morbidity, such as facial paralysis, are examples of secondary outcome indicators. (29)(30)(31) Acoustic Schwannoma patients can currently be managed using 3 different methods including radiotherapy/radiosurgery, resection, and conservative treatment. If a patient has a small tumor, few or no symptoms, a poor general health state, or if they are elderly, many doctors will opt for a conservative approach, although this can still cause hearing loss over time.…”
Section: Discussionmentioning
confidence: 99%
“…Hearing preservation and treatment-related morbidity, such as facial paralysis, are examples of secondary outcome indicators. (29)(30)(31) Acoustic Schwannoma patients can currently be managed using 3 different methods including radiotherapy/radiosurgery, resection, and conservative treatment. If a patient has a small tumor, few or no symptoms, a poor general health state, or if they are elderly, many doctors will opt for a conservative approach, although this can still cause hearing loss over time.…”
Section: Discussionmentioning
confidence: 99%
“…This technique of therapeutic exercise is distinguished by the utilization of diagonal patterns and the use of sensory cues-specifically proprioceptive, cutaneous, visual, and aural stimuli-to elicit or augment motor response. 8,9 Scapular PNF is used in two diagonal directions: anterior elevation-posterior depression and posterior elevation-anterior depression. Techniques of scapular PNF can be utilized to target-stretch or target-strengthen specific muscles since they involve functional or diagonal patterns for exercising.…”
Section: Introductionmentioning
confidence: 99%
“…14 Wang reported that studies on the effectiveness of PNFbased treatment have been both supportive and conflicting and that very few studies on pelvic facilitation for gait improvement existed. 9,12,15 Although there have been many studies using PNF for stroke, sports injuries, and musculoskeletal disorders. [16][17][18][19] Little research has been done on the effects of the intervention on the scapular movements and walking of stroke patients when it is applied to their scapular adductors.…”
Section: Introductionmentioning
confidence: 99%